Work/Family Conflict and Career Advancement : Demographic Differences as Moderators among IT Employees - Thriveni Kumari, K. (Prabandhan: Indian Journal of Management, 2022)
India’s information technology (IT) is the world’s largest sourcing destination, providing direct and indirect employment for more than 10 million people. It is seen that the IT sector in India always looks for career advancement. This study analyzed the work/family conflict of Indian IT employees and its influence on career advancement with demographic variables: age, gender, and marital status as moderators. The data were gathered from 392 respondents employed in Indian IT organizations. With the help of SPSS 21.0, the data were analyzed with descriptive statistics, correlation, and hierarchical regression, and the Hayes methodology and interaction software explained the moderators. It was observed that career advancement and work/family conflict had a favorable association which may vary in a particular state. It was also revealed that age acted as a moderator of all demographic differences selected in the study. Therefore, the article suggested that work/family conflict may positively or negatively influence career advancement.